Structure–behaviour correlations between two genetically closely related snail species. Issue 1 (22nd January 2020) - Le Ferrand, H.; Morii, Y.
Abstract : Species, through their structure and composition, have evolved to respond to environmental constraints. Predator–prey interactions are among environmental pressures that can lead to speciation, but it remains unclear how this pressure can be related to the material structure and performance. Recently, two land snails, Karaftohelix editha and Karaftohelix gainesi, were found to exhibit divergent phenotypes and responses to predation despite sharing the same habitat and most of their genome. Indeed, under attack from a beetle, K. editha snails retract into their shell whereas K. gainesi snails swing their shell. In this paper, we looked at the microstructure, composition, morphology and mechanics of the shells of those two species and discuss potential relationships between material structure and the snail defence behaviour. The results of this study provide additional arguments for the role of predator–prey interactions on speciation, as well as an unusual approach for the design of biomimetic structures adapted to a particular function.